Constructions territoriales et dynamiques patrimoniales dans le périurbain de Porto-Novo (Bénin) - Cédric Tafuri (Projets de Paysage)
The Porto-Novo region in West Africa is part of a growing conurbation in South-Eastern Benin. In the same way as in the city of Porto-Novo - the political capital of the country, which for some years has been undergoing a major dynamic heritagisation process - a spontaneous movement of identification and promotion of tangible and intangible cultural assets has emerged in the small municipalities of the Porto-Novo suburbs which have been marked by a profound re-composition of their landscapes and a redefining of their functions while undergoing a decentralisation process. The sacred forests of the Porto-Novo countryside, some of which are reservoirs of biodiversity, bear witness to the renewal of religious practices attached to the customary Vodun religion which have survived despite the rapid and predatory encroachment of urbanization. These wooded areas close to the city have many different forms today although their overall surface area has decreased; they also sometimes adapt to the modern context and to ongoing cultural transformations. In a context of religious diversity and of a revival of traditions in Benin since the 1990s, the recognition of these small forests as part of the cultural heritage may help protect them.